Humeral head necrosis associated to shaft non-union with massive bone loss: a case report - Manzotti, Alfonso; Brioschi, Davide; Grassi, Miriam; Biazzo, Alessio; Cerveri, Pietro (Acta Biomedica Atenei Parmensis, 2020)
Humeral non-union is a rare complication in shaft fractures, as well as humeral head necrosis is a possible complication in fracture involving the proximal third especially in four-part fractures. The presence of head osteonecrosis and diaphyseal non-union in the same arm represents a formidable challenge for an orthopaedic surgeon. We could not find any similar report in the literature dealing with this issue thus far.We present a case of a 65 years old woman referred to our hospital being affected by an atrophic humeral diaphyseal non-union with a massive bone loss (>10cm) associated to a humeral head osteonecrosis following a previous surgical procedures with a clear loosening of the hardware. At our institution,she was treated with hardware removal and insertion of a diaphyseal antibiotic spacer with Gentamycin for 2 months suspecting an active septic process at the union site despite negative cultural exams. Finally, she was treated with a cemented modular humeral megaprosthesis. At 20 months follow up, the patient, despite a reduced shoulder range of motion, referred to a pain-free recovery to an almost normal lifestyle, including car driving with no major disturbances.This case suggests that, in extreme selected cases following several failed treatments, megaprosthesis can represent a viable solution, especially in huge bone loss associated to joint degeneration, to ensure an acceptable return to a normal lifestyle.